Efficient utilization of higher-lying excited states to trigger charge-transfer events - Bouit, Pierre-Antoine; Spänig, Fabian; Kuzmanich, Gregory; Krokos, Evangelos; Oelsner, Christian; Garcia-Garibay, Miguel A.; Delgado, Juan Luis; Martin, Nazario; Guldi, Dirk Michael (Chemistry - A European Journal, 2010)
Several new fullerene-heptamethine conjugates, which absorb as far as into the infrared spectrum as 800 nm, have been synthesized and fully characterized by physicochemical means. In terms of optical and electrochemical characteristics, appreciable electronic coupling between both electroactive species is deduced. The latter also reflect the excited-state features. To this end, time-resolved, transient absorption measurements revealed that photoexcitation is followed by a sequence of charge-transfer events which evolve from higher singlet excited states (i.e., S-fast charge transfer) and the lowest singlet excited state of the heptamethine cyanine (i.e., S - slow charge transfer), as the electron donor, to either a covalently linked C or C as the electron acceptor. Finally, charge transfer from photoexcited C/ C completes the charge-transfer sequence. The slow internal conversion within the light-harvesting heptamethine cyanine and the strong electronic coupling between the individual constituents are particularly beneficial to this process. © 2010 Wiley-VCH Verlag GmbH&Co. KGaA, Weinheim.